Perception of equality and discrimination in Physical Education in Secondary School students - León Reyes, Borys Bismark; Galeano-Rojas, Dilan; Agulló-Hernández, Ana; Farias-Valenzuela, Claudio; del Val Martín, Pablo; Valdivia-Moral, Pedro (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The purpose of this work was to assess the perception of equal treatment and discrimination in secondary school students and examine the assessment of the different methodological factors that influence equal treatment and discrimination in PE. The sample was made up of 706 students (375 men and 331 women) with an average age of 13.05 years (SD= .93). The data collection instrument was the Questionnaire of Perception of Equality and Discrimination in PE and the analysis was performed using the Kolmogorov-Smirnov normality test and the Mann-Whitney U test for comparison of means. The results show that there are significant differences in the perception of equal treatment with higher mean values in girls and in the perception of discrimination with higher scores in boys. In turn, in the methodological factors related to sexist language and feedback, there are differences by sex that corroborate the greater perception of discrimination in boys and equality in girls. In conclusion, the forms of interaction used by the teacher have great influence on the students' perceptions in relation to gender stereotypes in the context of PE.